Menelaah Peran Alat Musik Melayu Jambi dalam Melestarikan Tradisi dan Kearifan Lokal - Archila Az-Zahra Komarudin; Dea Sri Ayu; Amalluna Umaya Rozalih; Bunga Revalina; Muhammad Bintang Anugerah; Syairul Bahar; Farkhan Abdurochim Alfaruq (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
The traditional Malay musical instruments of Jambi represent an important cultural heritage that plays a significant role in preserving the continuity of local traditions and wisdom within the Malay community of Jambi Province. Instruments such as the Gambus, Kelintang Kayu, Rebana, Serdam, and Serangko serve not only as sources of entertainment but also carry symbolic, spiritual, and social meanings that are deeply connected to local customs. This study aims to examine the role of Jambi Malay musical instruments in safeguarding tradition and local wisdom by analyzing their identity, musical structure, social–spiritual functions, and the transformation of traditional music within modern contexts. The findings indicate that Jambi’s traditional musical instruments not only represent cultural identity but also serve as a medium for preserving customs, strengthening social bonds, educating moral values, and expressing religious devotion. The transformation of traditional music through contemporary and digital innovations further helps maintain its relevance for younger generations. Thus, Jambi Malay musical instruments remain dynamic cultural elements that continue to play a vital role in upholding the continuity of local traditions and wisdom.